READING COMPREHENSION LEVEL AND STUDY SKILLS COMPETENCE OF THE ALTERNATIVE LEARNING SYSTEM (ALS) CLIENTELE - Labarrete, Rufo A (PUPIL: International Journal of Teaching, Education and Learning, 2019)
This study aimed to assess the reading comprehension level and study skills competencies of the Alternative Learning System-Accreditation and Equivalency (ALS-A&E) clientele. It utilized the descriptive-quantitative research design. Data were obtained from various adopted reading passages. Of the four reading dimensions, the clientele registered a good performance in the literal level but poorly performed in the inferential, evaluative, and creative dimensions. As to their study skills competencies, outlining and semantic mapping were their top concerns but they were nevertheless good in locating thesis statement and very good in book parts familiarization. Considering these findings, it is the imperative for the ALS implementers to revisit their pedagogic practices relative to the teaching of reading as a macro language skill especially on the areas were their clientele need instructional related interventions.